Doxycycline and Autogenous Bone in Repair of Critical-Size Defects - Lucateli, Ribamar Lazanha; Marciano, Marina Angelica; Ferreira, Sabrina [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Camilleri, Josette; Mariano, Ronaldo Celio (Lippincott Williams & Wilkins, 2018)
Purpose: The association of doxycycline (DOX) and autogenous bone on repair of critical-size defects was evaluated. Materials and Methods: Fifty albino rats were divided into 5 groups (n = 10). A 5-mm diameter defect was treated with: control (CO)-blood clot; DOX in Natrosol (NAT)-10% gel; NAT-gel; particulate autogenous bone (PAB); and PAB + DOX - PAB associated with 10% DOX gel. The animals were euthanized at 4 and 8 weeks postoperatively. Histomorphometric analysis was performed to assess the percentage of new bone in the defect area. Statistical analysis of the results was performed using analysis of variance and the Tukey test (P < 0.05). Results: The results showed that new bone formation was limited to the margins of the defect. At 4 and 8 weeks, the group PAB + DOX showed higher bone formation (38.59% and 47.86%, respectively), with statistical difference in comparison with the CO (19.52%) at 4 weeks and CO (18.80%), DOX (22.05%), and NAT (15.89%) at 8 weeks (P < 0.05). Conclusions: The association of 10% DOX with autogenous bone significantly improved bone healing in critical-size defects.
Keywords: bone regeneration; bone graft; osseous defects